1593. Antimicrobial Activity of Ceftazidime-Avibactam and Comparator Agents Against OXA-48 β-lactamase–Producing Enterobacterales Collected in International Medical Centers, Including the United States, in 2017–2018. (31st December 2020) - Lin, Lynn-Yao; Debabov, Dmitri; Chang, William
Abstract: Background: OXA-48 is a carbapenemase with low-level hydrolytic activity toward cephalosporins. This study evaluated in vitro activities of ceftazidime-avibactam (CAZ-AVI), meropenem (MEM), meropenem-vaborbactam (MVB), ceftolozane-tazobactam (C/T), and other antimicrobial agents against 113 OXA-48-producing Enterobacterales with multiple resistance mechanisms collected in a 2017– 2018 global surveillance program. Methods: Nonduplicate clinical isolates of 113 Enterobacterales were collected from medical centers in 25 countries in 2017– 2018. In vitro susceptibility tests were performed by broth microdilution with a custom-made panel consisting of CAZ-AVI, ceftazidime (CAZ), MEM, MVB, C/T, colistin (COL), gentamicin (GEN), levofloxacin (LEV), and amikacin (AMK). Whole genome sequencing or quantitative PCR data were used to analyze resistance mechanisms, such as OXA-48, extended-spectrum β-lactamase (ESBL), original-spectrum β-lactamase (OSBL), and AmpC β-lactamase. Clinical and Laboratory Standards Institute breakpoints were applied for susceptibility interpretations. Results: Of 113 OXA-48–producing clinical isolates, 20 carried OXA-48 alone. The remaining 93 isolates carried additional β-lactamases, including 63 with ESBL (CTX-M-15) + OSBL (SHV, TEM), 15 with AmpC (DHA, AAC, CMY) + ESBL (CTX-M-15), and 15 with OSBL (SHV, TEM). 99.1% (all but 1) of all isolates tested were susceptible to CAZ-AVI, whereas 71.7%, 17.7%, and 14.2% were susceptible to MVB, MEM, and C/T, respectively. Among isolates harboring multiple resistance mechanisms (OXA-48 + ESBL + OSBL; n=63), 98.4%, 69.8%, 11.1%, and 7.9% were susceptible to CAZ-AVI, MVB, MEM, and C/T, respectively. Among isolates carrying OXA-48 + AmpC + ESBL + OSBL (n=15), 100%, 66.7%, 13.3%, and 13.3% were susceptible to CAZ-AVI, MVB, MEM, and C/T, respectively (Table). Aminoglycosides (AMK and GEN) and other β-lactams (eg, CAZ) were 20%–90% active against these isolates. COL was the second most effective comparator, inhibiting 83.2% of these isolates. Table Conclusion: CAZ-AVI was the most effective agent in this study compared with other antibiotics, including β-lactams, β-lactam–β-lactamase inhibitor combinations, aminoglycosides, and COL, against OXA-48-producing Enterobacterales carrying multiple β-lactamases. Disclosures: Lynn-Yao Lin, MS, AbbVie (Employee) Dmitri Debabov, PhD, AbbVie (Employee) William Chang, BS, AbbVie (Employee)